Evaluasi Pertumbuhan Uji Provenans Eucalyptus urophylla S.T. Blake Umur 20 Tahun di Lad Krating, Chachoengsao, Thailand) - Indi Hendraswari; Suree Bhumibhamon (Jurnal Ilmu Kehutanan, 2009)
Evaluation of Provenance Trial of Eucalyptus urophylla S.T. Blake Growth Age 20-Year-old in Lad Krating , Chachoengsao Province, Thailand